2020
DOI: 10.3390/v12030358
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Strain Diversity of Multi-Host RNA Viruses that Infect a Wide Range of Pollinators and Associates is Shaped by Geographic Origins

Abstract: Emerging viruses have caused concerns about pollinator population declines, as multi-host RNA viruses may pose a health threat to pollinators and associated arthropods. In order to understand the ecology and impact these viruses have, we studied their host range and determined to what extent host and spatial variation affect strain diversity. Firstly, we used RT-PCR to screen pollinators and associates, including honey bees (Apis mellifera) and invasive Argentine ants (Linepithema humile), for virus presence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 80 publications
4
40
0
Order By: Relevance
“…First, the present study demonstrates that DWV persists in the longhorn crazy ant in all "abundant collection" regions, yet the level of prevalence is generally low. As all colonies of this ant were collected from sites geographically distant from any known apiary, such a low level of prevalence is expected and consistent with previous studies concerning invasive ant species (red imported fire ant [17] and Argentine ant [18]). Payne et al [17] found that DWV is four to five times less prevalent in ants collected from non-apiary sites than those from apiary sites.…”
Section: Dwv Prevalence In Globally Invasive Antssupporting
confidence: 88%
See 1 more Smart Citation
“…First, the present study demonstrates that DWV persists in the longhorn crazy ant in all "abundant collection" regions, yet the level of prevalence is generally low. As all colonies of this ant were collected from sites geographically distant from any known apiary, such a low level of prevalence is expected and consistent with previous studies concerning invasive ant species (red imported fire ant [17] and Argentine ant [18]). Payne et al [17] found that DWV is four to five times less prevalent in ants collected from non-apiary sites than those from apiary sites.…”
Section: Dwv Prevalence In Globally Invasive Antssupporting
confidence: 88%
“…Figueroa et al [ 13 ] and Alger et al [ 5 ] extended such a hypothesis and showed that flowers serve as a hub for transmitting honey bee diseases to other pollinators, suggesting that the circulation of honey bee viruses in the pollinator community may be more common than previously thought [ 14 , 15 ]. Indeed, other minor or non-pollinator insect species—such as ants—were also reported to test positive for several honey bee viruses [ 7 , 16 , 17 , 18 ]. This provides additional support to the hypothesis of interspecific associations likely serving as a conduit for virus transmission, given that ants are frequently found to interact with honey bees via activities such as raiding honey bee broods, scavenging honey bees and competing on floral resources [ 7 , 9 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition the high ABPV and IAPV prevalence that we observed in wild bees is to be considered with the ability of ABPV to infect ant species, thereby reducing emergence and colony size, and impairing their locomotion and movement speed [ 59 ]. Ants were also supposed to be host for the close KBV [ 58 ]. Then, viruses from the AKI-complex are clearly not restricted to the honey bee.…”
Section: Discussionmentioning
confidence: 99%
“…[ 47 ]. All viruses from the AKI-complex replicate in Bombus [ 46 , 54 , 105 , 106 ], and negative replicative forms were also detected in Vespa velutina [ 68 , 107 ], as well as bees from the Halictidae family [ 46 ] and several ant species [ 58 , 59 ]. Finally, BQCV has been shown to replicate in Bombus spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation